Ta’ṡir Taṭbîq Waṣîlah al-Ta’lîm al-Lughah al-Arabiyyah “Factile” li Tarqiyyah Mahârah al-Istimâ’ - Zulfa Amalia; Junaedi Junaedi; Saefullah Azhari (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose-The purpose of the researchers is to discuss the title